Echinophora tenuifolia subsp. sibthorpiana—Study of the Histochemical Localization of Essential Oil - Stanislava Ivanova; Stanislav Dyankov; Diana Karcheva-Bahchevanska; Velislava Todorova; Yoana Georgieva; Niko Benbassat; Kalin Ivanov (Molecules, 2023)
Background: Echinophora tenuifolia L. subsp. sibthorpiana is a perennial, aromatic plant used in traditional folk medicine and cuisine of the Mediterranean and the Middle East. However, scholars have not fully studied the pharmacological potential of the herb, and the scientific data on this plant species are limited. This study aimed to evaluate the chemical composition of the essential oil (EO) obtained from the aerial parts of E. tenuifolia subsp. sibthorpiana growing wild in Bulgaria and to perform histochemical analysis. Methods: A microscopic histochemical analysis and gas chromatography with mass spectrometry were performed. Results: The histochemical analysis confirmed the presence of terpenes in the stem and leaf of E. tenuifolia subsp. sibthorpiana. The phenylpropanoid methyleugenol was identified as the main compound in the EO, representing 48.13% of the total oil composition. There were also found considerable amounts of monoterpene hydrocarbons, representing 41.68% of the total EO. Alpha-phellandrene, o-cymene, and β-phellandrene were the most abundant monoterpene hydrocarbons. Conclusion: This is the first histochemical analysis performed on E. tenuifolia subsp. sibthorpiana. This is the first report of the EO composition from Bulgarian E. tenuifolia subsp. sibthorpiana, and our results indicate some future possibilities for evaluating of the biological activity of the EO of E. tenuifolia subsp. sibthorpiana and highlight the potential future use of the EO of this plant species. E. tenuifolia L. subsp. sibthorpiana EO possesses a good potential for use as a biopesticide and repellent an environmentally friendly alternative of synthetic pesticides.